Measuring competitiveness of companies in the field of food industry in Bosnia and Herzegovina - Puška, Adis; Beganović, Admir I. (Oeconomica Jadertina, 2020)
Increasing changes in the market have caused companies to turn largely to lowering all unnecessary costs in order to be competitive. Competitiveness is a concept that is being explored progressively. This paper offered a way to measure enterprise competitiveness. Competitiveness testing was conducted on companies in the field of food industry in Bosnia and Herzegovina (B&H). A systematic sample was used. The collected data were analysed by factor analysis. Out of a total of 8 dimensions used, the factor analysis performed a reduction of these dimensions and led to the final 6 dimensions that determine the competitiveness of companies in the field of food industry in B&H. The obtained results showed that these dimensions stand out from others and represent the competitiveness of the company. These dimensions are: cost competition, price competition, product and business process innovation, customer satisfaction, delivery reliability and organisational learning. This research will help managers of companies in the food industry in B&H to improve market competitiveness. The methodology used in this paper will help other companies to improve competitiveness and achieve better results in the market.